Authentication and Discrimination of Whiskies of High Commercial Value by Pattern Recognition - Cantarelli, Miguel Angel (2014)
An analytical method for a rapid and non-destructive classification and authentication of whiskies of high commercial value based on trademark and years of aging is presented. Molecular absorption spectroscopy was performed with a minimum manipulation of the sample. Different conditions previous to the chemometric analysis, such as dilution and pH effect were studied. Fifteen commercial trademarks of whiskies with different years of aging were acquired from the local market. The pattern recognition was performed using principal component analysis (PCA), linear discriminant analysis (LDA) and partial least squares discriminant analysis (PLS-DA) to obtain models that allowed the classification and discrimination of whiskies based in trademarks and years of aging respectively. Results show that by LDA, a mean of 99.15% of samples were correctly classified according to trademark. On the other hand, by PLS-DA a 100% of correct classification and discrimination was achieved with several aging labels (6, 8, 12 and 15 years of aging).